Competing Effects of Mountain Uplift and Landslide Erosion Over Earthquake Cycles. Issue 5 (22nd May 2019) - Li, Gen; West, A. Joshua; Qiu, Hongrui
Abstract: Large earthquakes can construct mountainous topography by inducing rock uplift but also erode mountains by causing landslides. Observations following the 2008 Wenchuan earthquake show that landslide volumes in some cases match seismically induced uplift, raising questions about how the actions of individual earthquakes accumulate to build topography. Here we model the two‐dimensional surface displacement field generated over a full earthquake cycle accounting for coseismic deformation, postseismic relaxation, landslide erosion, and erosion‐induced isostatic compensation. We explore the related volume balance across different seismotectonic and topographic conditions and revisit the Wenchuan case in this context. The ratio (Ω) between landslide erosion and uplift is most sensitive to parameters determining landslide volumes (particularly earthquake magnitude M w, seismic energy source depth, and failure susceptibility, as well as the seismological factor responsible for triggering landslides), and is moderately sensitive to the effective elastic thickness of lithosphere, T e . For a specified magnitude, more erosive events (higher Ω) tend to occur at shallower depth, in thicker‐ T e lithosphere, and in steeper, more landslide‐prone landscapes. For given landscape and seismotectonic conditions, the volumes of both landslides and uplift to first order positively scale with M w and seismic moment M o . However, higher M w earthquakes generate lower landslide and uplift volumes per unit M o, suggesting lower efficiency in the use of seismic energy to drive topographic change. With our model, we calculate the long‐term average seismic volume balance for the eastern Tibetan region and find that the net topographic effect of earthquakes in this region tends to be constructive rather than erosive. Overall, destructive events are rare when considering processes over the full earthquake cycle, although they are more likely if only considering the coseismic volume budget (as was the case for the 2008 Wenchuan earthquake where landsliding substantially offset coseismic uplift). Irrespective of the net budget, our results suggest that the erosive power of earthquakes plays an important role in mountain belt evolution, including by influencing structures and spatial patterns of deformation, for example affecting the wavelength of topography. Key Points: Develop a generalized modeling framework evaluating earthquake volume balance considering seismic deformation, landslide erosion, and erosion‐induced isostacy Comprehensively evaluate earthquake volume balance across varying topographic and seismotectonic conditions Find the overall topographic effect of earthquake cycles in the eastern Tibetan region to be constructive